1999
DOI: 10.1007/s004649901183
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of video thoracoscopy in the management of spontaneous and postoperation chylothorax

Abstract: We suggest that VATS should be considered the treatment of choice for spontaneous chylothorax and could be indicated earlier in postoperation chylothorax.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…It has been demonstrated that thoracic duct ligation may be successfully performed by using video-assisted thoracoscopy in order to avoid a thoracotomy, with apparently lesser postoperative pain, shorter recovery time and hospital stay [9][10][11][12][13][14][15][16][17][18][19][20][21]. However, this technique has not gained wide acceptance at date due to the rarity of this intervention.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been demonstrated that thoracic duct ligation may be successfully performed by using video-assisted thoracoscopy in order to avoid a thoracotomy, with apparently lesser postoperative pain, shorter recovery time and hospital stay [9][10][11][12][13][14][15][16][17][18][19][20][21]. However, this technique has not gained wide acceptance at date due to the rarity of this intervention.…”
Section: Discussionmentioning
confidence: 98%
“…Although thoracic duct ligation has been accomplished by thoracoscopy, most surgeons rely on open procedure through a right thoracotomy. Thoracic duct ligation performed by a VATS approach has not gained wide acceptance since most reports deal with anecdotal observations and are based mainly on case reports [5,[9][10][11][12][13][14][15][16][17][18][19][20][21]. We report our experience with thoracoscopic right supra-diaphragmatic thoracic duct ligation in a small series www.elsevier.com/locate/ejcts European Journal of Cardio-thoracic Surgery 29 (2006) 810-814 of six patients presenting with recurrent or persisting nontraumatic chylothorax.…”
Section: Introductionmentioning
confidence: 99%
“…7 VATS has became the preferred surgical method to deal with this complication because of its easy manageability and low morbidity. 8 It was performed under local anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Although limited in extent, our experience suggests that the present technique (right thoracoscopy in adults) can be performed safely and quickly for aortic surgery-related traumatic chylo-leakage, and that it is perfectly effective. Thus, more prompt surgical management using the present method may be recommendable [6][7][8], particularly in elderly or infant patients who are vulnerable and cannot tolerate prolonged chylous leakage. …”
Section: Commentsmentioning
confidence: 99%